International Immigration and Labor Regulation - Adam Levai; Riccardo Turati (Institute of Labor Economics (IZA), 2024)
The existing literature investigating the labor market impact of immigration assumes, implicitly or explicitly, that the law or labor regulation is exogenous to immigration. To test this assumption, we build a novel workers' protection measure based on 36 labor law variables that capture labor regulation over a sample of 70 developed and developing countries from 1970 to 2010. Exploiting a dynamic panel setting using both internal and external instruments, we establish a new result: immigrants' norms and experience of labor regulation influence the evolution of host countries labor law regulation. This effect is particularly strong for two components of workers' protection: worker representation laws and employment forms laws. Our main results are consistent with suggestive evidence on the transmission of preferences from migrants to their offspring (vertical transmission), and from migrants to natives or local political parties (horizontal transmission). Finally, we find that the size of the immigrant population per se has a small and negligible impact on host country labor market regulation.
Keywords: J61; K31; F22; 330; international migration; labor market institutions; labor regulation; legal transplants